PREPARATION OF NANOCOMPFEXES OF CURCUMINOIDS WITH CYCFODEXTRINS AND CHARACTERISTICS OF ITS STRUCTURAL AND FUNCTIONAL PROPERTIES - M. A. Kapustin; A. S. Chubarova; I. A. Evdokimov; A. D. Lodigin; S. V. Lodigina; V. G. Cigankov; A. M. Bondaruk; V. P. Kurchenko (Современная наука и инновации)
Spicy-aromatic plants are an important source of biologically active substances when creating junctional food products. Among them, an important place is occupied by the rhizomes of turmeric Curcuma longa L., from which curcuminoid extract is obtained.